Prevalence and determinants of anaemia in pregnant women receiving antenatal care at a tertiary referral hospital in Northern Ghana - Wemakor, Anthony (BMC Pregnancy Childbirth, 2019)
BACKGROUND: Anaemia during pregnancy is a major public health problem in developing countries. It is important to regularly monitor haemoglobin level in pregnancy and factors associated with it to inform clinical and preventive services. The aim of this study was to assess the prevalence and determinants of anaemia in pregnant women attending antenatal clinic (ANC) of a tertiary referral hospital in Northern Ghana. METHODS: An analytical cross-sectional study involving 400 pregnant women receiving antenatal care in Tamale Teaching Hospital was conducted. Using a semi-structured questionnaire and 24-h dietary recall, data were collected on socio-demographic characteristics, health practices, dietary diversity, anaemia knowledge and haemoglobin level of the women. Anaemia was defined as haemoglobin concentration less than 11 g/dl. Chi-square test and logistic regression analysis were used to identify the independent determinants of pregnancy anaemia. RESULTS: The mean age and haemoglobin of the women were 28.3 (±4.5) years and 10.81 (±1.41) g/dl respectively. About half of the women 50.8% [95% Confidence Interval (CI): 45.8–55.7] were anaemic and the prevalence of anaemia increased with pregnancy trimester. Among a host of socio-demographic, dietary, and preventive health service factors evaluated, the women’s knowledge on anaemia and pregnancy trimester at interview were the independent determinants of anaemia in pregnancy. Compared to women of the highest anaemia knowledge tertile, women belonging to the lowest (AOR = 2.63, 95% CI: 1.50–4.61) and middle (AOR = 1.92, 95% CI: 1.12–3.27) anaemia knowledge tertiles were about 3 and 2 times more likely to be anaemic respectively. Similarly, women in third trimester of pregnancy were about 4 times more likely to be anaemic compared to those in first trimester at the time of interview (AOR = 3.57, 95% CI: 1.91–6.67). CONCLUSIONS: There is a high prevalence of anaemia, which increases with pregnancy trimester, in pregnant women attending ANC in a tertiary referral hospital in Northern Ghana. The women’s knowledge on anaemia and pregnancy trimester at the time of interview are associated with their anaemia status. The high prevalence of anaemia in pregnancy needs urgent intervention to prevent the occurrence of adverse maternal and neonatal outcomes. Education on anaemia should be intensified at ANCs.